MODELING PROCESS OF STOCK DRAINAGE DYNAMICS HYDROCARBONS (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article provides information on determining the field model by refining the hydrodynamic calculation of data obtained from the field and refining the variability of the productive formation when designing technological indicators for the operation of oil and gas fields.